The Role of Work Engagement in The Effect of Job Demands and Job Resources on Employee Performance at The Regional Financial and Asset Management Agency of Bontang City - Muhammad Ibrahim; Siti Maria; Dirga Lestari (MASI Mandiri Edukasi, 2026)
Regional financial management institutions operate under high administrative pressure, strict regulatory standards, and demanding accountability requirements, which may influence employees' psychological conditions and performance outcomes. However, limited empirical research has simultaneously examined the roles of job demands and job resources in shaping employee performance through work engagement within local government institutions. This study aims to analyze the role of work engagement in mediating the relationship between job demands, job resources, and employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Bontang City. This research employed a quantitative, survey-based approach. Data were collected from 45 employees selected through purposive sampling based on their involvement in financial and asset management functions. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique to test both direct and mediating relationships among variables. The findings reveal that job demands negatively affect work engagement and employee performance, whereas job resources positively influence both. Work engagement also has a significant positive effect on employee performance and serves as a mediating variable in the relationships between job demands and performance, as well as between job resources and performance. These results confirm the central role of work engagement as a psychological mechanism that translates work conditions into performance outcomes in public sector financial institutions. The study highlights the importance of balancing job demands with adequate organizational resources to sustain employee engagement and enhance performance in regional government settings